Juxtahepatic venous injuries are not AAST Grade V injuries if there is no contrast extravasation - Vijayan Purushothaman; Kirthi Sathyakumar; Vignesh Kumar; Srujan Lam Sharma (Journal of Current Research in Scientific Medicine)
Background: The organ injury scale (OIS) for liver trauma by the American Association of the Surgery of Trauma (AAST) was last updated in 2018 with new “imaging criteria” that continued to grade juxtahepatic venous (JHV) injuries, regardless of presence or absence of active bleeding, as Grade V. We hypothesized that JHV injury found on imaging, in the absence of active bleeding, should not be considered Grade V based on location alone. The aim of the study was to compare the outcomes of patients classified as AAST-OIS Grade V liver injuries based purely on JHV location, with patients who had AAST-OIS Grade I–III liver injuries. Materials and Methods: A retrospective analysis of 121 patients with liver injury from the TReCS database (June 2020–May 2023) was conducted. Patients underwent contrast-enhanced dual-phase computed tomography scans on admission were reviewed by both radiologists and surgeons. Patients diagnosed with JHV injuries (JHV – with no contrast extravasation [CE]) and patients with low-grade injuries (OIS I–III) were compared for baseline data on age, gender, injury severity score (ISS) scoring, injury mechanism, length of hospital stay, and liver-related complications. Results: Of 121 patients identified, 66 had Grade I–III injuries and 21 had Grade V injuries due to JHV location alone. Three of the latter group had CE and were excluded. Heterogeneity was compared between the two groups for age (P = 0.634), gender (P = 0.964), mechanisms (P = 0.346), and ISS (P = 0.068). The median length of stay for the JHV (with no CE) group was 4.5 days and 6.00 days for the OIS Grade I–III group (P = 0.233). One patient in the JHV group had hemobilia, and there were no other liver-related complications in the cohort. Conclusion: Our findings suggest that the “imaging” criterion of “JHV” injuries, in the absence of extravasation or significant disruption, may be safely revised to a lower grade on the AAST-OIS for liver injuries.